Application of Linear Programming Based Transportation Models to Optimize Natural Disaster Relief Distribution - Saddam Husein; Zulhamsyah Fachrurrazi Nasution; Ema Sri Rezeki; Afdhal Ahkrizal (UIN Sumatera Utara, 2026)
Disaster relief distribution is a complex logistical problem and requires optimal planning for targeted and efficient distribution. This study aims to apply a linear programming-based transportation model to optimize aid distribution from several warehouses to affected shelters, with clearly defined constraints based on field conditions. The method used is a quantitative approach through simulation supported by empirical data representing post-disaster conditions. The model is formulated in an objective function to minimize total distribution costs with warehouse capacity and shelter requirements constraints. The process solution model is carried out using LINDO (Linear, Interactive, Discrete Optimizer) optimization software to ensure calculation accuracy. The optimization results show a cost reduction from 1,550 to 650 units, or a savings of 58.06% while still satisfying all supply and demand constraints. These findings indicate that the linear programming-based transportation model is effective in increasing aid distribution efficiency and supporting more targeted logistics decision-making.